Comparison and the effectiveness of tourism policies between Macedonia and Serbia - Galovski, Dejan (Turizam, 2018)
Tourism is one of the most growing industries and engine of the national economies. In the recent years, every tourist destination and countries as a one tourist destination implement many marketing policy and strategies to promote and developed their national tourism products. In this paper will compare Macedonian and Serbian tourism marketing policy and will see what kind of efforts and which activities and resources are used for promotion and development of national tourism products. Macedonia and Serbia are neighbor countries and they offer same types of tourism as a mountain, city and religious tourism and also exchange of tourist from both countries is on a high level. Also will analyze who create and implemented tourism marketing policy in each country. In detail, will analyze the assets which are sort out for development and promotion of Macedonian and Serbian tourism products and their effect on the increasing or decreasing number of tourists. The effectiveness of tourism policy of both destinations will analyze through competitiveness index and quantitative analyze. With Travel and Tourism Competitiveness Index (TTCI) by World Economic Forum will compare the competitiveness of both countries. Also with quantitative analyze of tourism indicators will see which destination is more successful. The period that will analyze will be from 2009 to the 2015 year.